An NRAS mutation in primary malignant melanoma of the lung: a case report - Takashi Hibiya; Meiro Tanaka; Mai Matsumura; Ayako Aoki; Tadashi Ikegami; Koji Okudela; Naomi Kawano; Kenichi Ohashi (BMC, 2020)
Abstract Background Primary malignant melanoma of the lung (PML) is extremely rare. No precursor lesions of PML have been identified, and little is known about the genetic mutations associated with the disease. Typically, 15-20% of malignant melanomas possess NRAS gene mutations, but no cases of NRAS-mutated PML have been reported in the English literature. We present a case of PML involving an NRAS mutation. Case presentation Clinical summary A 74-year-old Japanese female presented with worsening dyspnea and was admitted to hospital. Computed tomography (CT) revealed a right lung (S10) mass and pleural dissemination. Cytology of the pleural effusion in the right lung was performed, and malignant melanoma or clear cell sarcoma was suspected. A dermatological examination and gallium scintigraphy were conducted to determine the primary tumor site, but no suspicious lesions, expect for the right lung mass, were found. After admission, CT showed complicating bilateral pneumonia, and an antibiotic drug was administered, but the pleural effusion got worse. About 2 weeks later, the patient died of respiratory failure and cardiac arrest. An autopsy was performed to determine the histological diagnosis. Autopsy findings A 26x15x20-mm black and pale yellow mass was found in the right lower lobe. Many disseminated nodules were found in the right lobe. The tumor had invaded the right diaphragm. Subcarinal lymph node metastasis was also detected. Immunohistochemically, the tumor cells exhibited positivity for S-100 and HMB45 staining. The patient was diagnosed with malignant melanoma. Sanger sequencing of the tumor detected an NRAS mutation. Conclusions We found an NRAS D54N mutation in PML, which has not been reported previously anywhere in the world. Previous reports indicated that most cases of PML can be classified into the triple-wild-type, but BRAF mutation status was only analyzed in a few cases. We should analyze the mutation patterns of PML to determine whether any subtypes other than the triple-wild-type exist. PML might be a form of de novo cancer.